Antioxidant, antibacterial and cytotoxic activity of Caulerpa racemosa (Forsskål) J. Agardh and Ulva (Enteromorpha) intestinalis L. - Uddin, S Aftab; Akter, S; Hossen, S; Rahman, MA (Bangladesh Journal of Scientific and Industrial Research, 2020)
Seaweeds are fresh sources of phytochemical compounds with immense medicinal potential, which have attracted the attention of agriculture, aquaculture and the pharmaceutical industry. The aim of this study was to test the antioxidant, antibacterial and cytotoxic activity and screening the phytochemical properties of methanol crude extract from two green seaweeds Caulerpa racemosa (Forsskål) J.Agardh and Ulva (Enteromorpha) intestinalis L. The antioxidant and cytotoxic activity of these seaweeds were assessed by 2,2diphenyl, 1-picryl hydrazyl (DPPH) free radical scavenging technique and brine shrimp lethality bioassay method, respectively. The antibacterial activities against Vibrio fluvialis was determined using the standard disc diffusion method. The U. intestinalis showed higher total phenolic content with the value of 149.87 ± 18.17 mg of GAE/g than 73.95 ± 16.09 mg of GAE/g of C. racemosa. However, the recorded inhibition concentration (IC50) to corresponding standards ascorbic acid of C. racemosa and U. intestinalis were 119.62 and 34.274 μg/mL, respectively. The values were statistically significant (p <0.05) compared to the reference antioxidative agent ascorbic acid. In antibacterial assay, C. racemosa extract showed higher inhibition zone (22.65 ± 0.58 mm) than U. intestinalis (17± 0.28 mm). Moreover, U. intestinalis exhibited a lower LC50 value than C. racemosa in cytotoxic activity. Phytochemical analysis revealed that these two seaweeds have alkaloids, flavonoids, glycosides, phenols, saponins, steroids and tannins. Bangladesh J. Sci. Ind. Res.55(4), 237-244, 2020